Association Between Structural Change Over Eighteen Months and Subsequent Symptom Change in Middle‐Aged Patients Treated for Meniscal Tear. Issue 2 (21st October 2022) - Katz, Jeffrey N.; Collins, Jamie E.; Jones, Morgan; Spindler, Kurt P.; Marx, Robert G.; Mandl, Lisa A.; Levy, Bruce A.; Wright, Rick; Jarraya, Mohamed; Guermazi, Ali; MacFarlane, Lindsey A.; Losina, Elena; et al.
Abstract : Objective: Middle‐aged subjects with meniscal tear treated with arthroscopic partial meniscectomy (APM) experience greater progression of damage to joint structures on imaging than subjects treated nonoperatively. It is unclear whether these changes are clinically relevant. The goal of this study was to assess whether worsening in magnetic resonance imaging (MRI)–assessed tissue damage over 18 months leads to subsequent worsening in knee pain over the subsequent 3.5 years. Methods: We used data from the Meniscal Tear in Osteoarthritis Research (MeTeOR) trial of APM versus physical therapy for subjects ages ≥45 years with knee pain, cartilage damage, and meniscal tear. We assessed whether change in cartilage surface area damage score (and other structural measures) from baseline to 18 months, assessed on MRI with the MRI Osteoarthritis Knee Score (MOAKS) system, was associated with change in Knee Injury and Osteoarthritis Outcome Score (KOOS) pain score (range 0–100; 100 = worst) from 18 to 60 months. Results: The primary analysis included 168 subjects with complete MRI data at baseline and 18 months and KOOS data at 18 and 60 months. We did not observe clinically important associations between change in cartilage surface area score between baseline and 18 months and change in pain scores from 18 to 60 months. Pain scores in the worst tertile for cartilage surface area damage score progression worsened by 0.45 points more than in the best tertile (95% confidence interval –4.45, 5.35). Similarly, we did not observe clinically important associations between changes in bone marrow lesions, osteophytes, or synovitis and subsequent pain. Conclusion: We did not observe clinically important associations between early changes in cartilage damage and other structural measures and worsening in pain over the subsequent 3.5 years. Further follow‐up is required to assess this association over a longer follow‐up period.